2014
DOI: 10.1177/1479164114539712
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin is independently associated with metabolic syndrome and microvascular complications in type 2 diabetes mellitus

Abstract: Aims: Osteoprotegerin (OPG) is a glycoprotein from tumour necrosis factor receptor superfamily, responsible for osteoclastogenesis inhibition and associated with arterial calcification and stiffness. We describe the association between metabolic syndrome (MS) and OPG in type 2 diabetes mellitus patients. Methodology: We consecutively enrolled 1220 patients from our institution's Diabetes Centre from August 2011. Anthropometric data such as fasting blood/urine were obtained, and OPG was measured by enzyme-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…Osteoprotegerin, a member of the tumor necrosis factor receptor family, is released from vascular endothelial cells in response to inflammatory stimuli and is associated with increased cardiovascular risk and diabetes complications . Previously, we showed in our study cohort that higher OPG concentrations were associated with the risk of metabolic syndrome (MS) and microvascular complications . Pigment epithelium‐derived factor, a key adipokine, induces insulin resistance and inflammation signals and is associated with diabetes and obesity‐related disorders .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Osteoprotegerin, a member of the tumor necrosis factor receptor family, is released from vascular endothelial cells in response to inflammatory stimuli and is associated with increased cardiovascular risk and diabetes complications . Previously, we showed in our study cohort that higher OPG concentrations were associated with the risk of metabolic syndrome (MS) and microvascular complications . Pigment epithelium‐derived factor, a key adipokine, induces insulin resistance and inflammation signals and is associated with diabetes and obesity‐related disorders .…”
Section: Discussionmentioning
confidence: 59%
“…33 Previously, we showed in our study cohort that higher OPG concentrations were associated with the risk of metabolic syndrome (MS) and microvascular complications. 34 Pigment epithelium-derived factor, a key adipokine, induces insulin resistance and inflammation signals and is associated with diabetes and obesity-related disorders. 35,36 The ethnic differences in baseline LTL and inverse associations between changes in obesity indices and LTL observed in the present study were not substantially attenuated after further adjustment for hs-CRP, PEDF, and OPG, suggesting that this association may not be due to obesity-related inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, elevated circulating levels of OPG have been reported in T2DM, particularly in the presence of microvascular complications (Knudsen et al, 2003), with several studies (Nybo et al, 2010; Tavintharan et al, 2014; Terekeci et al, 2009), but not all (Bourron et al, 2014), having shown an association between increased levels of OPG and peripheral neuropathy. The mechanism of this association was not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of diabetic neuropathy is multifactorial with metabolic, neurovascular, and inflammatory components. Three studies in persons with diabetes have demonstrated an association between higher OPG levels and peripheral neuropathy (Nybo, Poulsen, Grauslund, Henriksen, & Rasmussen, 2010; Tavintharan et al, 2014; Terekeci et al, 2009). OPN, in rodents, has been shown to be upregulated in denervated motor pathways with increased OPN protein expression in denervated Schwann cells following nerve injury (Wright et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic vascular disease is the leading cause of death and disability in diabetic patients; 30-40% of the patients are subject to at least one vascular complications after 10 years (Tavintharan et al, 2014). Numerous studies have shown the association of diabetes mellitus vascular complications with oxidative stress in endothelial cells and endothelial cells derived from progenitor cells (mainly in the bone marrow) (Kizub et al, 2014;Prieto et al, 2014;Yiu and Tse, 2014).…”
Section: Introductionmentioning
confidence: 99%